Studi Pelacakan Kinerja Lulusan Jurusan Ilmu Ekonomi dan Studi Pembangunan (IESP) Fakultas Ekonomi Dan Bisnis Universitas Mataram - Daeng, Akung; Suriadi, Irwan; Masrun, Masrun (Jurnal Ekonomi dan Bisnis, 2017)
This study is an attempt to analyze 1). Describing a graduate alumni of IESP (old college Alumni IESP, the waiting period to get a first job), 2) How to Evaluate the performance of graduates by the user in the majors IESP the faculty of economics and business, University of Mataram. The research method in this study conducted with descriptive evaluative. Subjects were IESP graduate of the Faculty of Economics and Business, University of Mataram in 2011-2016 as many as 30 alumni. Data analysis techniques used in this research is descriptive analysis with quantitative approach to give a picture related to graduates or alumni IESP Faculty of Economics and Business, University of Mataram The results of this study indicate that assessment alumni users of the performance of graduates (Alumni) courses IESP where performance alumni higher in users of alumni who give good value (B) was the professionalism of the alumni as many as 22 people (73%), while users who value a very good (SB) is the highest for Integrity 37% and the use of IT by the alumni of 11 people (37%) of alumni rated excellent (SB) while the performance of the alumni of the lowest according to the user is the expertise of English graduates with enough value (C) of 50% alumni and less value (K) of 4 people (4%).